Penguatan Karakter melalui Kegiatan Keterampilan Public Speaking - Ayuningtyas, Fitria; Intyaswati, Drina; Tayibnapis, Radita Gora; Saputra, Windhi Tia (Jurnal SOLMA, 2025)
ound: Public speaking encompasses addressing a large crowd and articulating a message with clarity, persuasiveness, and the ability to sway the audience. Public speaking enables individuals to conquer phobias, enhance communication skills, and cultivate self-confidence. Method: This Community Service employs the working premise of the Participatory Action Research (PAR) approach, with 20 participants from the first batch of Graphic Design class in 2023 from PPKD West Jakarta. Results: PKM must consistently consider three dimensions simultaneously: the satisfaction of practical demands and issue resolution, the advancement of knowledge and community diversity, and the dynamics of social diversity transformation. The purpose of evaluation in this activity is to ensure it is guided effectively and meets the anticipated objectives of all stakeholders. The initial session focused on the Fundamentals of Public Speaking, while the subsequent session concentrated on Enhancing Character Through Activities that Develop Public Speaking Skills, accompanied by examples. The subsequent session involved a brief review of the material presented to assess any changes in participants' abilities, particularly in public speaking skills. An evaluation of 20 participants indicated a notable enhancement in their public speaking proficiency and self-confidence. Conclusion: Public speaking enhances self-confidence, critical thinking abilities, empathy, and social skills in individuals. Consequently, this skill is valuable not only in academic or professional settings but also in daily life.